Intrahepatic T‐Cell Receptor β Immune Repertoire Is Essential for Liver Regeneration. Issue 5 (27th October 2018) - Liang, Qing; Liu, Zeyuan; Zhu, Chao; Wang, Bin; Liu, Xiaoke; Yang, Yanan; Lv, Xue; Mu, Haiyu; Wang, Kejia
Abstract : T lymphocytes synergize with the cellular immune system to promote hepatocyte regeneration. The T‐cell receptor (TCR) immune repertoire is closely associated with the host immune response and regenerative proliferation. High‐throughput sequencing of TCR provides deep insight into monitoring the immune microenvironment. Here, we aimed to determine the role of the TCRβ immune repertoire in liver regeneration (LR). We investigated hepatic regeneration in TCRβ chain‐deficient ( tcrb –/– ) mice by two‐thirds partial hepatectomy (PHx) method. Our results demonstrated that tcrb –/– mice revealed a reduced capacity for LR, which was characterized by impaired hepatocyte proliferation and enhanced hepatocyte apoptosis. Dysregulation of inflammatory signaling activation and inflammatory factors was observed in regenerated tcrb –/– livers. Simultaneously, significantly altered immunocyte levels and aberrant cytokine levels were observed during hepatic regeneration. In addition, we first determined the profile of the TCRβ immune repertoire during LR, indicating that PHx resulted in remarkably lower TCRβ diversity in intrahepatic T lymphocytes. Conclusion: Taken together, our data suggest that TCRβ deficiency gives a rise to aberrant intrahepatic immune microenvironment that impairs LR, and the TCRβ reconstitution is required for hepatic immunocyte recruitment and activation during LR.